Drosophila Uri, a PPIα binding protein, is essential for viability, maintenance of DNA integrity and normal transcriptional activity - Kirchner, J; Vissi, E; Gross, S; Szoor, B; Rudenko, A; Alphey, L; White-Cooper, H (BioMed Central, 2008)
Background: Protein phosphatase 1 (PP1) is involved in diverse cellular processes, and is targeted to substrates via interaction with many different protein binding partners. PP1 catalytic subunits (PP1c) fall into PP1α and PP1β subfamilies based on sequence analysis, however very few PP1c binding proteins have been demonstrated to discriminate between PP1α and PP1β. Results: URI (unconventional prefoldin RPB5 interactor) is a conserved molecular chaperone implicated in a variety of cellular processes, including the transcriptional response to nutrient signalling and maintenance of DNA integrity. We show that Drosophila Uri binds PP1α with much higher affinity than PP1β, and that this ability to discriminate between PP1c forms is conserved to humans. Most Uri is cytoplasmic, however we found some protein associated with active RNAPII on chromatin. We generated a uri loss of function allele, and show that uri is essential for viability in Drosophila. uri mutants have transcriptional defects, reduced cell viability and differentiation in the germline, and accumulate DNA damage in their nuclei. Conclusion: Uri is the first PP1α specific binding protein to be described in Drosophila. Uri protein plays a role in transcriptional regulation. Activity of uri is required to maintain DNA integrity and cell survival in normal development.